KESEHATAN MENTAL ANAK SD DI TENGAH FENOMENA BULLYING: KAJIAN SYSTEMATIC LITERATURE REVIEW - Yunita Ratna Dewi; Haifaturrahmah; Sukron Fujiaturrahman (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the impact of bullying behavior on the mental health of elementary school children through a Systematic Literature Review (SLR) method. The literature sources were obtained from various internationally indexed databases, including Scopus, DOAJ, Scispace, and Google Scholar, covering publications from 2017 to 2025. The selection procedure was conducted systematically using strict inclusion and exclusion criteria to ensure relevant and representative findings. The analysis reveals that bullying behavior, particularly verbal and social forms, has a significant impact on the mental health of elementary school children. The effects include an increased risk of emotional problems such as anxiety, depression, post-traumatic stress disorder (PTSD), low self-esteem, and suicidal ideation. Furthermore, bullying contributes to reduced learning motivation, social isolation, and difficulties in adapting to the school environment. Based on the findings, it can be concluded that bullying serves as a major risk factor that hinders children’s psychological well-being. Therefore, comprehensive actions involving schools, families, and communities are required to establish a safe, supportive, and mentally healthy educational environment for children.